2009
DOI: 10.1128/cmr.00012-09
|View full text |Cite
|
Sign up to set email alerts
|

Food-Borne Trematodiases

Abstract: SUMMARY An estimated 750 million people are at risk of infections with food-borne trematodes, which comprise liver flukes (Clonorchis sinensis, Fasciola gigantica, Fasciola hepatica, Opisthorchis felineus, and Opisthorchis viverrini), lung flukes (Paragonimus spp.), and intestinal flukes (e.g., Echinostoma spp., Fasciolopsis buski, and the heterophyids). Food-borne trematodiases pose a significant public health and economic problem, yet these diseases are often neglected. In this review, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
398
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 566 publications
(413 citation statements)
references
References 105 publications
0
398
0
15
Order By: Relevance
“…Splenomegaly is a rare finding (23) . Acute symptoms seem to occur more frequently in O. felineus infections than in C. sinensis and O. viverrini, and fever is sometimes seen (7) .…”
Section: Clinical Manifestations Clonorchiasis and Opsithorchiasismentioning
confidence: 99%
See 4 more Smart Citations
“…Splenomegaly is a rare finding (23) . Acute symptoms seem to occur more frequently in O. felineus infections than in C. sinensis and O. viverrini, and fever is sometimes seen (7) .…”
Section: Clinical Manifestations Clonorchiasis and Opsithorchiasismentioning
confidence: 99%
“…An estimated 10 million people are infected worldwide, 80% of whom reside in Thailand (7) . A study in Thailand showed O. viverrini infection rates ranging between 2 and 71% in different districts (15) .…”
Section: Affected Populationsmentioning
confidence: 99%
See 3 more Smart Citations